METB-09. METABOLIC ADAPTATION TO CHRONIC HYPOXIA IN GLIOBLASTOMA CELLS - Caflisch, Laura (Neuro Oncol, 2017)
BACKGROUND: Long-term metabolic adaptations may account for the ability of GBM tumor cells to adapt to the stress of hypoxia over time to survive and grow aggressively. Our patient-derived GBM cells grow more aggressively in vitro during long-term hypoxia compared to normoxia despite initial stress. This suggests that these cells can adapt directly to hypoxic environments over time, rather than simply relying on evasion of hypoxia through angiogenesis and migration. METHODS: Cells were cultured in 2% hypoxia for at least 2-5 weeks. Using mass spectrometry, NanoSight extracellular vesicle analysis, and metabolic inhibitors, metabolic patterns associated with hypoxia were determined, with focus on lipid metabolism. In addition, patient tumors with previously quantified hypoxic burdens (using carbonic anhydrase IX) were profiled for lipid metabolites. RESULTS: In vitro metabolite levels supported an expected increased flux of metabolites through anaerobic glycolysis (p<0.0013 for increased G3P and lactic acid) and decreased flux through the citric acid cycle (p=0.027 for decreased malic acid) during hypoxia compared to normoxia, as well as decreased flux through mitochondrial fatty acid oxidation (p<0.0033 for increased isobutyryl-L-carnitine, L-acetylcarnitine, hexanoylcarnitine), increased flux through glutathione metabolism (p<0.000057 for increased S-lactoylglutathione, decreased glutathione), and an overall decrease in cardiolipins and gangliosides (p<0.0062). Patient tumors with higher hypoxic burdens were correlated with a decrease in very long chain fatty acids in the serum (r(2)=0.50). The metabolic inhibitor TVB (fatty acid synthase inhibitor) induced an increase in extracellular vesicles, with an increased proportion of exosome-sized vesicles (50-120 nm) specifically during hypoxia (p=0.042). CONCLUSION: These findings reflect changes in metabolic pathways, including lipid metabolism, the citric acid cycle, fatty acid oxidation, glutathione recycling, and extracellular vesicle synthesis, that could be potentially targeted to increase the sensitivity of hypoxic tumors to treatment, particularly in combination with treatments that increase hypoxia such as anti-angiogenic agents.